Agents of Change and Contentious Agents Interwoven Narratives in the Visual Representations of the Protester in News Magazine Covers - Delia Dumitrica; Alexandra Schwinges (International Journal of Communication, 2022)
This article examines the visual representations of the protester on the covers of Der Spiegel and Time (2010–2020). Drawing from the protest paradigm literature and literature on the role of visuals in protest, the article performs a qualitative content analysis of a corpus of 47 relevant covers. The analysis reveals the coexistence of different narratives: on the one hand, the protesting citizen appears as a powerful political agent, commanding attention with his determination and dedication to the cause. While this hopeful image can appease worries around the alleged apathy of the civic body, it also re-legitimizes Western democracies as accountable to and shaped by their citizenry. On the other hand, the protesting citizen can also be a danger to democracies, as it threatens to destabilize the political field. Two trends are noteworthy here: the individualizing and individualistic lens through which collective action is increasingly represented on news magazine covers; and the rise of the female protester as a politically significant actor.